Epistemological Disjunctivism's Genuine Access Problem. (30th June 2015) - Kraft, Tim
Abstract Epistemological disjunctivism, as defended by, for example, McDowell, Neta and Pritchard, is the view that epistemic justification can be – and in paradigmatic cases of perceptual knowledge actually is – both factive (i.e., entails that the belief is true) and reflectively accessible (i.e., can be known by reflection alone). One major problem for this view is the access problem: apparently, epistemological disjunctivism entails that ordinary external world propositions can be known by reflection alone. According to epistemological disjunctivism, seeing that the sun is shining is reflectively accessible and seeing that the sun is shining entails that it is. Assuming closure of reflective knowledge under known entailment it is also reflectively knowable that the sun is shining. Drawing on joint work with Neta, Pritchard replies that disjunctivism is not committed to this absurdity, but only to the possibility of reflective access to empirical reasons. In this article I offer an interpretation of this reply, but also an objection to it: my interpretation is based on applying the source/content distinction to epistemic reasons. My objection is based on arguing that the access problem is a problem for any (non‐sceptical) version of access internalism. Although Pritchard's reply solves the general access problem, it does not solve the access problem that is generated by the specific commitments of epistemological disjunctivism. Due to the transparency of self‐knowledge of propositional perception, epistemological disjunctivism cannot meet a central requirement for applying the source/content distinction.